HUBUNGAN STATUS GIZI DENGAN HASIL BELAJAR PENJASORKES SISWA PUTRI KELAS X SMA NEGERI 1 LUBUK DALAM KABUPATEN SIAK - M Ismail M Ismail; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: The problem in this research is whether there is a relationship of nutritional status with learning achievement of physical education. The goal is to find out how big the correlation between nutritional status with learning achievement of physical education. The technique of sampling performed with purposive sampling of 26 female students class ten which is devided into 5 classes.This research using a correlation technique. Then, the data are tested using the test of normality, test the product moment correlation test, test of significance on the level of significance of α = 0.05. Test of normality of variabels X, L0maks (0,102) < Ltabel (0,173), and testing normality of variabels Y, L0maks (0,116) < Ltabel (0,173) in other words at a confidence level of 95% of normal data and concluded the results showed: there is a significant relationship between eye nutritional status with learning achievement of physical education, with correlation r= 0.444, where rhitung > rtabel or 0.444 > 0,388. and such relations are categorized normal . Thus, Ho rejected and Ha accepted.Key Word: Correlation, Nutritional Status, Learning Achievement